Coronavirus disease 2019 (COVID -19) and its impact on dental practice: a review - Ramírez-Velásquez, Mariela (2020)
The presence of the new pandemic COVID-19 or SARS-CoV-2 shows the need to adopt measures that minimize, prevent, and control the risk of infection and the spread of the virus in dental practice. Therefore, the objective of this article is to establish the repercussions in different areas of dental care facing the presence of the virus, in relation to the practice of dental infection control, its contagion characteristics (in different stomatological scenarios), dental procedures and possible considerations during the pandemic. Concluding that in dental practice, emergency procedures should be prioritized to those patients without respiratory symptoms in addition to the prior evaluation to rule out any symptomatology related to the virus, protecting the health of professionals and patients who interact during the dental consultation.